Implementing moving object capability in a two-phase Eulerian model for sediment transport applications - Puig Montella, Eduard; Bonamy, Cyrille; Chauchat, Julien; Hsu, Tian-Jian (OpenFOAM® Journal, 2024)
This article presents the validation of a modified 6DoF solver which includes the contribution of particle forces on rigid objects. The solver is an extension of sedFoam, employed for a wide range of sediment transport applications. The first validation consists in a simple case of a sphere freely falling in a pure fluid. Then, the same sphere is submerged in a fluid with suspended particles. The next step involves placing a granular bed under the sphere to study its arrest due to particle-particle interactions. Lastly, the trajectory of a cylinder immersed in a uniform granular flow is studied to emphasize the lift and drag forces exerted by the particle phase on the solid object. Results show that overSedDyMFoam accurately reproduces experimental/numerical measurements successfully capturing the behavior of solid objects subjected to granular and fluid forces. This implementation is a significant step towards understanding complex interactions between fluid, particles, and structures.